Navigating heterogeneity in meta-analysis: methods for identification and management - Ilmawan, Muhammad (Deka in Medicine, 2024)
Although meta-analysis is a powerful way to synthesize research findings from multiple studies, the problem of heterogeneity usually arises due to variation in study outcomes. Differences between studies regarding heterogeneity in results can arise from populations, interventions, outcome measures, and methodologies both within and between the studies. This article aims to provide an overview of the methods for identifying and dealing with heterogeneity in meta-analyses to ensure accurate and reliable conclusions. The article aims to describe the application of several statistical methods for detecting heterogeneity, namely the Q statistic and the I² statistic. The Q statistic is used to test whether observed variability in effect sizes exceeds chance expectations, while the I² statistic quantifies the proportion of variability due to heterogeneity. Other methods include the DerSimonian-Laird between-studies variance in random-effects models and the T and T² methods, which use both observed and expected information about effect size dispersion. Methods for dealing with heterogeneity are discussed, including choices between using fixed- versus random-effects models, and techniques for assessing and dealing with outliers using methods such as the Hedges technique. Additionally, the article explores methods to investigate sources of heterogeneity through subgroup analysis and meta-regression. Recognizing limitations such as residual heterogeneity, publication bias, and study quality is also important in making meta-analytical findings more robust. In conclusion, these methods enable researchers to more effectively address heterogeneity issues in meta-analyses, thereby providing more reliable and valid conclusions that contribute to evidence-based practice